Economic Transformation in Slovenia: From a Model Example to the Default Edge - Libor Žídek (Review of Economic Perspectives, 2016)
The Slovenian economy appeared on the brink of bankruptcy at the end of 2013. The situation was caused by high level of classified debts in state-owned banks. This can be seen as surprising because Slovenia used to be (for a long time) considered as a (textbook) example of the gradualist transformation approach. The goal of this article is first to describe the transformation process in the country and consequently to determine causes of the economic problems that resulted in the 2013 crisis. The article concludes that the economic problems were rooted already in the specific functioning of the centrally planned system in Yugoslavia. These specifics had a direct influence on the transformation process in the country and stood behind the application of gradualism. Among the most telling features of gradualism were slow privatization, cold attitude towards foreign investment and the foremost lasting casual economic environment caused by behaviour of the state-owned banks. My conclusion is that the country's economic problems can be ascribed to gradualism and that they are a clear example of the path dependence development.
Keywords: 330; Slovenia; economic transformation; banking system; gradualism